Analysis of Increasing Knowledge, Attitudes, and Behaviors for Type 2 Diabetes Complication Prevention - Rusmini Rusmini; Edy Suyanto; Nurwahidah Nurwahidah; Ratih Putri Maharani (Ridwan Institute, 2023)
Diabetes mellitus is characterized by elevated blood sugar levels due to either a lack of insulin or decreased cellular sensitivity to insulin. Type 2 diabetes accounts for most (90%) of all diabetes cases. Diabetes mellitus is a significant contributor to mortality, mainly because it leads to complications such as atherosclerosis, coronary heart disease, and stroke. The research was designed as a quasi-experiment, employing a pre-test and post-test with a control group. The analysis included the use of Wilcoxon and Mann-Whitney tests. The sampling method used was purposive sampling, involving 100 participants. The results of the data analysis using the Wilcoxon test in the treatment group indicated a p-value of 0.000 (p<0.05) for the knowledge, attitude, and behavior variables. In the control group, a p-value of 0.002 (p<0.05) was observed for the knowledge variable, while p-values of 0.001 (p<0.05) were found for the attitude and behavior variables. These findings support the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (H0), suggesting that the use of video media and modules positively impacts increasing knowledge, attitudes, and behaviors aimed at preventing complications. When examining the intervention group and control group using the Mann-Whitney Test, the p-value of 0.000 was less than 0.002, indicating that the use of video educational media in the intervention group significantly improved knowledge. Likewise, the statistical tests on attitudes in both groups revealed a p-value of 0.000, which was less than 0.001, signifying that video educational media significantly improved attitudes in the intervention group. Finally, the analysis of behavioral tests demonstrated a p-value of 0.000, which was less than 0.001 in both groups, highlighting the greater impact of video educational media in enhancing behavior. In conclusion, video educational media and modules effectively enhance knowledge, attitudes, and behavior in individuals with type 2 diabetes mellitus. However, video education is more influential in improving these aspects compared to other methods.